Development of Sipitung Media (Smart Calculating Action) on Summary Materials in Improving Students' Learning Outcomes in Class 1 Students of SD Negeri 2 Kumbang - M. Irwan Mansyuriadi; Rudi Purwanto (Classroom Experiences, 2023)
This study aims to examine the feasibility, practicality, and effectiveness of the developed media. In this study the method used is research and development (R&D) because the product being developed is learning media in real form, not software engineering. The model used in this research and development is the ADDIE model which consists of 5 stages: analysis, design, development, implementation, and evaluation. In the analysis phase, researchers analyzed needs based on observations and interviews with elementary school mathematics teachers. The design stage is the stage in determining the selection of materials, determining the design, and the initial design of the Sipitung learning media (smart count action) to be made. Development, namely the feasibility testing stage of the sipitung media (smart count action) carried out by material experts and design experts obtained a score of 98.3% with very feasible criteria. The implementation stage, namely the practicality test of sipitung media (smart count action) by giving a questionnaire to grade 1 mathematics teachers obtained a score of 100% and 15 grade 1 students obtained a score of 94.83% with very practical criteria to use. The final stage is evaluation, namely testing the effectiveness of the Sipitung media (smart count action) in improving student learning outcomes with an average score before using the media of 56.33 and after using it 90.33.